2021
DOI: 10.3390/met11060989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron Carbide Addition on Wear Resistance of Aluminum Matrix Composites Fabricated by Stir Casting and Hot Rolling Processes

Abstract: In this study, to evaluate the effect of boron carbide (B4C) addition on the wear performance of aluminum (Al), Al6061 and 5, 10, and 20 vol.% B4C/Al6061 composites were manufactured using the stir casting and hot rolling processes. B4C particles were randomly dispersed during the stir casting process; then, B4C particles were arranged in the rolling direction using a hot rolling process to further improve the B4C dispersion and wear resistance of the composites. Furthermore, a continuous interfacial layer bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…However, it was seen that the wear track and depth of the Ti60Si15Zn20B5 material were less than the Ti60Si20Zn20 material. This observation was in agreement with the results of [45]. The pitted structure and grooves on the worn trajectory were also formed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, it was seen that the wear track and depth of the Ti60Si15Zn20B5 material were less than the Ti60Si20Zn20 material. This observation was in agreement with the results of [45]. The pitted structure and grooves on the worn trajectory were also formed.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the material having the highest hardness value, generally showed the minimum weight loss. Therefore, it can be stated that the hardness results and weight losses of the wear test are inversely related as stated in [45]. Moreover, the fact that the Ti45Si15Zn20B20 material, which had the most crystalline structure according to the XRD results, also had the highest micro-hardness and therefore the lowest weight loss, showing that all analyses in this study were supporting each other.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Notably many industries are profitable and society is getting benefit from stronger, lighter and cost-effective materials (1,2) . From household appliances to nuclear industry composites are popular, especially in aerospace and military industries where weight is a key factor (3,4) . Composite materials are the field of interest for many scholars all over the world, as they are an essential part of latest trending technology.…”
Section: Introductionmentioning
confidence: 99%